CpG methylation frequency of TET2, GRIA2, and CDKN2A genes in the North Atlantic fin whale varies with age and between populations. Issue 4 (12th April 2021) - García‐Vernet, Raquel; Martín, Berta; Peinado, Miguel A.; Víkingsson, Gísli; Riutort, Marta; Aguilar, Alex
Abstract: Recovery rates for baleen whales that were decimated by exploitation vary between species and populations. Age determination is critical for the understanding of recovery trends and population structure, but determining age in free‐ranging individuals remains challenging. Recent research has suggested that the methylation level of some genes in skin samples may provide age determinations with accuracy. We selected nine CpG sites from three genes ( TET2, CDKN2A, and GRIA2 ) and analyzed them in 40 skin samples from known‐age individuals pertaining to two different populations of fin whales from the North Atlantic. We observed significant correlations with age in five CpG sites. We used three of these CpG sites to perform an epigenetic age estimation. Predictions had a standard deviation of 2.94, but regression between observed and predicted ages showed a clear underestimation for older fin whales. For further development, we suggest: (1) screening for new CpG sites associated with age that exhibit higher variability between individuals, and (2) including older animals whenever the sampling allows it. We also observed subtle, but significant differences between the two populations studied in one of the CpG sites (TET2_CpG + 21). We attributed these differences to genetic differences or to the dissimilar environments that affect both populations.